Contraception method among pregnant women with HIV delivered in Cipto Mangunkusumo General Hospital, Jakarta, Indonesia - Junita Indarti; Shinta Pangestu; Adri Dwi Anggayana; Cherysa Rifiranda; Natasya Prameswari; Kristian Alda (Universitas Airlangga, 2022)
HIGHLIGHTS 1. HIV transmission from HIV positive mothers to their children should be reduced by strengthening family planning programs.2. Characteristics of contraceptive methods among women with HIV infection delivered in a tertiary hospital were investigated.3. IUD was the most common contraceptive method used by women with HIV infection. Its use was related to age, gravida and method of delivery. ABSTRACT Objectives: The aim of this study was to describe characteristics of contraceptive methods among women with HIV infection who delivered in a tertiary hospital. Materials and Methods: This was a cross-sectional study. The inclusion criteria were pregnant women with HIV infection who delivered in Cipto Mangunkusumo General Hospital (RSCM), Jakarta, Indonesia, from January 2016 to December 2020. Data were retrieved from medical records, registered HIV and laboratory result. The included data were demographic data, obstetric data, mode of delivery, contraception method, ARV history, and laboratory history of the mothers. Results: From January 2016 to December 2020 there were 119 HIV patients who delivered at the RSCM. Most of the subjects were 35 years old (84%), had low education (52.9%) and worked as housewives (76.5%). A total of 79.8% of the subjects were gravida >2 and most of the subjects delivered by caesarean section (87.3%). The choice of contraceptive methods were IUD (72.4%), tubectomy (26.8%) and implants (0.8%). There was a statistically significant relationship between contraceptive method with age (p 0.040), gravida (p 0.016) and delivery method (p 0.049) Conclusion: The most common contraceptive method was IUD. The choice of this method of contraception was related to age, gravida and method of delivery.